A New Approach to the Apocryphal Ladder of Jacob*. (March 2019) - Böttrich, Christfried
For a long time the apocryphal Ladder of Jacob was accessible only in arbitrarily selected translations. Without a critical edition and a comprehensive study of the whole textual segment, scholars were unable to evaluate its significance for Early Jewish and Christian literature. Since 2015/17, with the publication of a new critical edition and German translation (accompanied by a detailed introduction, footnote commentaries and appendices with related texts), a new approach to this important but hitherto widely unknown text has been made possible. This approach verifies the different layers or strata in the text, which are: a supposed Jewish apocalypse (mid-second century), a Christian expansion of the angels speech in light of the praeparatio evangelica tradition (fourth–seventh centuries), a Jewish mystical prayer (eleventh century) and the incorporation of this narrative block into the Tolkovaja Paleja together with a series of exegetical commentaries (end of the thirteenth century). In the light of the new approach, it can be said that the Ladder of Jacob is most of all an outstanding example of mutual relations between Jewish and Christian theology.